Use of strontium isotope ratios in geolocation of Guatemalan population: Potential role in identification of remains. Issue 5 (9th August 2022) - Austin, Ryan; Fowler, Gillian; Cooper, Jonathan J.; Perez Tanchez, Marco; Croxton, Ruth; Evans, Jane; Thompson, David F.
Abstract: Within post‐conflict communities, attempts to identify and repatriate unidentified and missing individuals poses a difficult task. As current forensic strategies commonly lack the capacity to provide region of origin assessments, forensic anthropologists/investigators are often unable to identify sources of DNA for kinship analysis. Using Thermal Ionization Mass Spectrometry (TIMS), hair samples from 10 volunteers were used to assess the variation in strontium isotope ratios ( 87 Sr/ 86 Sr) between extant people in Guatemala City and Coban; with a leach (external) and digest (dietary) signal analyzed for each sample. A two‐way anova demonstrated that the difference between 87 Sr/ 86 Sr of Guatemala City and Coban was statistically significant ( F [1, 16] = 259.839, p  < 0.05), with no statistically significant differences observed between leach and digest 87 Sr/ 86 Sr ( F [1, 16] = 4.319, p  = 0.054). Overall, individuals from Coban demonstrate 87 Sr/ 86 Sr comparable to previously recorded baseline values, demonstrating a minimal change in diet which is reflected in associated surveys. Volunteers from Guatemala City, however, show a marked shift in 87 Sr/ 86 Sr away from predicted values highlighting the potential influence of imported goods. The results here highlight the applicability of 87 Sr/ 86 Sr in hair to serve as a potential tool to support the identification of unknown individuals in Guatemala in a forensic context.